(untitled) (Baghdad Science Journal, 2012)
In this study a new ligand ,(potassium 2-carbomethoxy amino-5-trithiocarbonate 1,3,4-thiadiazole) (L) has been prepared from 2-carbomethoxy amino-5-mercapto 1,3,4-thiadiazole with CS2 in alkali media . The product has been isolated and characterized by appropriate physical measurements, vibrational and electronic spectroscopy. The ligand was used to prepare a number of complexes with some metal ions Co(II), Ni(II) and Cu(II). These complexes have been characterized by FT-IR, UV-Vis spectra, molar conductivity, magnetic susceptibility, melting points and atomic absorption measurements. The nickel and copper complexes have an octahedral geometry while cobalt complex has a tetrahedral geometry. The nature of bonding between the metal ion and the donor atom of the ligand was demonstrated through the calculated Racah parameter and other ligand field parameters, which have been calculated by using a suitable Tanaba-Sugano diagram The biological activity of the ligand and it’s complexes have been examined against two selected microorganisms Pseudomonas aeruginsa and Staphylococcus aureus using (10mM) and (5mM) in nutrient agar medium. The results were showed enhancement of activity of some complexes compared to that of the respective ligand, which were attributed to the synergetic effect between the metal ion and the ligand in addition to the difference in the structural varieties.